Trachurus symmetricus - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Trachurus symmetricus (Ayres, 1855). Jack Mackerel . To 81.3 cm (32 in) TL (Miller and Lea 1972). Pacific Ocean south of Aleutian Islands (Mecklenburg et al. 2002), and Gulf of Alaska to Gulf of California (Smith-Vaniz in Fischer et al. 1995) to Acapulco, Mexico (Palacios-Salgado et al. 2014). Primarily pelagic; depth: surface (Miller and Lea 1972), intertidal (Carlisle et al. 1960) and offshore to 403 m (1,320 ft (220 fm)) (Hart 1973)). The maximum depth of this species is unclear. For instance, in the NWFSC-FRAM database there are 30 records of catches deeper than 403 m, with a maximum depth of 1,172 m (3,844 ft). However, as all of these records are from bottom trawls it is not possible to differentiate between fish caught on the bottom and those caught in the midwaters during net deployment or retrieval. Although Trachurus murphyi Nichols, 1920, found off South America, is considered by some authors (e.g., Grove and Lavenberg 1997) to be a subspecies of T. symmetricus , DNA evidence indicates it is a separate species (Poulin et al. 2004). Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 156, DOI:10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008